Estruturas de fase geradas por órbitas complexas variando parâmetros reais - Araújo, José Rodolfo Bezerra Mesquita (2016)
This work is a computational mapping of the phase space of iterated maps. Initially, a review of the real Hénon map is presented, aiming at the identification of patterns in the stability regions of the parameter space. Then, the algorithm developed is extended to allow complex variables, while still requiring parameters to be real. This procedure permits the observation of different stable loci in phase space. Finally, developed tools and observations are applied in a comparative study of the generalized cubic Hénon map.